Effect of leaded glasses and thyroid shielding on cone beam CT radiation dose in an adult female phantom - Goren, AD; Prins, RD; Dauer, LT; Quinn, B; Al-Najjar, A; Faber, RD; Patchell, G; Branets, I; Colosi, DC (Dento-maxillo-facial radiology, 2013)
This study aims to demonstrate the effectiveness of leaded glasses in reducing the lens of eye dose and of lead thyroid collars in reducing the dose to the thyroid gland of an adult female from dental cone beam CT (CBCT). The effect of collimation on the radiation dose in head organs is also examined. Dose measurements were conducted by placing optically stimulated luminescent dosemeters in an anthropomorphic female phantom. Eye lens dose was measured by placing a dosemeter on the anterior surface of the phantom eye location. All exposures were performed on one commercially available dental CBCT machine, using selected collimation and exposure techniques. Each scan technique was performed without any lead shielding and then repeated with lead shielding in place. To calculate the percent reduction from lead shielding, the dose measured with lead shielding was divided by the dose measured without lead shielding. The percent reduction from collimation was calculated by comparing the dose measured with collimation to the dose measured without collimation. The dose to the internal eye for one of the scans without leaded glasses or thyroid shield was 0.450 cGy and with glasses and thyroid shield was 0.116 cGy (a 74% reduction). The reduction to the lens of the eye was from 0.396 cGy to 0.153 cGy (a 61% reduction). Without glasses or thyroid shield, the thyroid dose was 0.158 cGy; and when both glasses and shield were used, the thyroid dose was reduced to 0.091 cGy (a 42% reduction). Collimation alone reduced the dose to the brain by up to 91%, with a similar reduction in other organs. Based on these data, leaded glasses, thyroid collars and collimation minimize the dose to organs outside the field of view.